Evaluating the effectiveness of interactive radio instruction in teaching indigenous languages to native and non-native speakers in Nigeria - Fasinro, Kabiru Sasaenia; Akinpelu, Biodun; Alabi, Olaide B; Akinkuotu, Foluke. A.; Onowugbeda, Franklin Ufoma (African Perspectives of Research in Teaching and Learning Journal, 2024)
This study aimed to investigate the effect of interactive radio instruction on the academic achievement of native and non-native speakers taught indigenous languages. The study was quantitative research and a quasi-experimental design was employed, involving one experimental and one control group comprising 92 senior secondary class 2 students from two schools in Education District 5 of Lagos State. A Yoruba language achievement test (YLAT) was used for data collection, validated by experts, and tested for reliability with a coefficient of 0.85. Both groups underwent pretests, four weeks of treatment, and posttests. The experimental group, exposed to IRI, achieved a mean score (28.66, 12.25) significantly higher than the control group's mean score (12.92, 6.11). The result of the ANCOVA test on the post-test achievement scores showed that the difference in the performance between the students in the experimental class and control class was significant, F (1, 90) = 17.85; p < 0.05. The analysis revealed a significant difference in achievement between the IRI and lecture groups. These findings highlight the effect of IRI in learning Yoruba language. It was recommended that learners should be encouraged to practice the Indigenous languages outside the classroom through interaction with native speakers to immerse and strengthen their language skills and enhance comprehension.
Journal article article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 8, 2024
Keywords: Interactive Radio Instruction; Indigenous Language; Achievement; Yoruba Language; Linguistics, Experimental; Radio; Radio -- Problems, exercises, etc.; Academic achievement -- Nigeria; Indigenous peoples -- Languages